Varian Item Paket Chaki Birthday Party terhadap Perilaku Pembelian Paket Ulang Tahun Anak di Restoran Cepat Saji KFC Jember - Febrina Gerhani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Marketing activities are required to always be creative and innovative in competing to get interest from buyers. This study aims to determine the relationship between variants of the Chaki Birthday Party KFC Jember item on the behavior of purchasing children's birthday packages at KFC Jember fast food restaurants. The number of sample is 132 people with parents as the sample who filled in the questionnaire as a representative of the behavior shown by children towards the item variants of Chaki Birthday Party KFC Jember package. The research instrument was in the form of a questionnaire to determine the assessment of item variants of Chaki Birthday Party package and children's buying behavior. Simple statistical procedures were conducted in the form of percentage calculation and data descriptions to analyze data. The results of this study indicated that the most children behavior in determine buying activity were included in habitual buying behavior of 69.28%. In relation to the item variants offered and promoted by KFC Jember, 70.37% students showed interest and enthusiasm for the Chaki Birthday Party package item. Therefore, the interest and enthusiasm for Chaki Birthday Party package item variants encourages the buying behavior caused by habit due to the comfort and loyalty of children as consumers or potential consumers of the Chaki Birthday Party package. Keywords: Item Variants, Chaki Birthday Party KFC Package, Children Buying Behavior, Selling Strategy